PENGARUH EKSPOR NETO, KURS DOLLAR AMERIKA SERIKAT, PRODUK DOMESTIK BRUTO DAN UTANG LUAR NEGERI TERHADAP CADANGAN DEVISA INDONESIA TAHUN 1997-2016 - Yessi Ardianti, Dewa Ayu Made; Swara, Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Trade activity is defined as a process of exchange, arises because both countries see the advantages and benefits. It’s require important of payment that is foreign exchange reserves. This study aims to determine the effect of partial and then simultaneously between net export, US dollar, gdp, foreign debt to Indonesia's foreign exchange reserves. Another goal is to know the variables that have the most dominant influence on Indonesia's foreign exchange reserves. Multiple linear regression is used for analytical , and use secondary data period 1996-2016. Based on the test results, simultaneously net exports, US dollar, gdp and foreign debt significantly influence Indonesia's foreign exchange reserves period 1997-2016. Partially, foreign debt has a significant and positive influenc. Gdp, net exports, foreign debt, US dollar exchange rate hasn’t affected on foreign exchange reserves of Indonesia for analytical period of 1997-2016. The most dominant variable affecting foreign exchange reserves is foreign debt.